Sound, Image, Silence : Art and the Aural Imagination in the Atlantic World - Gaudio, Michael (Book collections on Project MUSE., 2019)
"Sound, Image, Silence explores how, over the course of three centuries, paintings, photographs and early silent films communicated the sounds and silences found in the New World to white audiences on the European continent. Through the representation of both landscapes and indigenous people, book explores the role of aural imagination as it pertains to the visualization of particular episodes of colonialism and oppression, but also tries to think seriously about how art historians should engage with sound in what is inherently a "mute" medium"--